Медіа-культура та відеоігри в Японії: розширена реальність та соціальний камуфляж - Томіта Хіденорі (Народна творчість та етнографія, 2009)
The author enters a reader in the modern world of games and facilities of visual communication, where a border is destroyed between the real and virtual. Attention is given to the negative influence of the use of media techniques of anime, so-called «twinkling» on the health and psyche of young generation of TV-viewers.